Analysis and Implementation of Signature Based Method and Structure File Based Method for File Carving - Anjar Afrizal; Niken Dwi Wahyu Cahyani; Erwid Musthofa Jadied (School of Computing, Telkom University, 2021)
File Carving is a data recovery technique based on file structure and content without relying on filesystem information or metadata. The problem in carving files is its high false positive value especially when the file is fragmented (either linear fragmented or non-linear fragmented). The aim of this study is to implement and analyze the performance of two file carving method (Signature Based and File Structure Based) as a solution to the problem of the carving process. By focusing on JPEG, GIF and PNG files, two datasets are used, namely: CFReDS Project (NIST Project) and Basic Data Carving Test (Nick Mikus Project). The analysis is based on the recovery performance (carving recall, supported recall, carving precision), execution time, and memory usage. From the recovery performance parameter, the File Structure Based method gets a higher overall value than the Signature Based method. However, based on the execution time performance parameter, the Signature Based method has better execution time and use fewer resources compared to the File Structure Based method.